Desenvolvimento de um estudo para a construção e sustentabilidade solar de um bastão para obtenção de dados periódicos do solo - Souto, Yago Daniel (Universidade Federal Rural do Semi-Árido, 2019)
Soil moisture or water content is expressed as the ratio of the mass of water contained in a soil sample to the mass of dry soil expressed in kilograms of water per kilogram of soil or, multiplying by 100, has in percentages. As with the soil moisture of a site, other quantities may be related to several factors, among which it is possible to cite the temperature. Thus, thriving in a study to obtain periodic soil data on the observation of moisture and temperature values can contribute satisfactorily to producer decision making when planning the beginning of a new crop cycle. The proposed study intends to develop a device with the sensitivity of materials or systems to environmental mechanisms /events of the potiguar semitic arid soil, and the samples for analysis would be the data obtained from the variations of these mechanisms such as time /temperature. In our research there will be the theoretical study of techniques for the operation and transmission of data to be captured by the environmental staff. From the results of this study it is expected the development of practical tools of values more accessible than those found in the market. The methodology of this proposal is likely to present patent-pending results and techniques. The results of this study will provide benefits to the society, since from this research we will be able to collaborate /contribute with the data collected by the staff, helping it and making it aware of the urgency of improving the habits and techniques of planting in the region of Pau dos Ferros (RN).
Development of a study for the construction and solar sustainability of a pole to obtain periodic soil data
Monografia
Keywords: Tecnologias ambientais; Sustentabilidade; Monitoramento ambiental; Instrumentação ambiental; Environmental technologies; Sustainability; Environmental monitoring; Environmental instrumentation.; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA